Students’ Perceptions of Reading Digital Texts at a Private University in Indonesia - Hastuti, Annisa Indri; Sumedi, Siti Hanna; Afiyattena, Nurul (Universitas Muhammadiyah Tangerang, 2025)
This study explored students’ perceptions of reading digital texts at a private university in Indonesia. This research aimed to explore students' perceptions while using digital text in reading activities. Furthermore, the researcher applied a case study as research design. Semi structure interviews and reflective notes were used to explore students' perceptions of reading digital texts then analyzed the data obtained with thematic analysis. In addition, this study highlights students' perceptions of the use of digital texts according to the philosophical theory of perception, hence it is found that the characteristics of digital texts namely, the flexibility and effectiveness of digital texts, digital texts are very flexible as they can be accessed anytime and anywhere through any devices. Digital text is very flexible from an accessibility perspective, easy to carry anywhere and easy to find.Digital text has a flexibility that led to the effectiveness for the readers to increase their interest in reading. Besides, reading materials are available in electronic media, providing students with various up to date materials and the latest information. This study emphasizedstudents’ perception that digital text is very flexible and effective for readers to use.